Enabling factors for green housing projects / Nur Atifah Bahruddin and Thuraiya Mohd - Nur Atifah, Bahruddin; Thuraiya, Mohd (Universiti Teknologi MARA, Perak, 2019)
Transformations of the housing industry in Malaysia deliver tremendous benefits. Currently, green housing received significant attention in Malaysia by introducing Green Building Index (GBI) as green rating tool for buildings. However, the implementation of green housing is quite low due to certain barriers. Thus, this research focusses on determining enabling factors that will be considered in developing green housing projects. The research conducted a questionnaire survey to the developers while data was analysed through the quantitative method. This research attempted to highlight the significant enabling factors being considered by developers in developing green housing projects.